Nature Relatedness Is Positively Associated With Dietary Diversity and Fruit and Vegetable Intake in an Urban Population. Issue 6 (July 2022) - Milliron, Brandy-Joe; Ward, Dane; Granche, Janeway; Mensinger, Janell; Stott, Dahlia; Chenault, Claire; Montalto, Franco; Ellis, Eugenia V.
Purpose: Feeling connected to nature, or nature relatedness (NR), can positively impact physical and psychological well-being. However, the relationship between NR and dietary behaviors has not been studied. This research examined the relationship between NR and dietary behaviors, including dietary diversity and fruit and vegetable intake. Design: Cross-sectional online survey study. Setting: Philadelphia, Pennsylvania. Subjects: Adults (n = 317) over 18 years who resided in Philadelphia, PA. Measures: The NR Scale was used to measure participants' connection to nature. It includes 21 items across three subscales: self, experience, and perspective (total and subscales range from 1 to 5). Dietary Diversity was assessed using the FAO's standardized tool (scores range from 0 to 9). To calculate dietary diversity, food groups reported were aggregated into nine food categories: starchy staples; dark green leafy vegetables; vitamin A rich fruits/vegetables; other fruits/vegetables; organ meat; meat/fish; eggs; legumes, nuts/seeds; and milk products. The NCI's 2-item CUP Fruit and Vegetable Screener was used to estimate daily fruit and vegetable intake (cups/day), and socio-demographic questions were asked. Analysis: Simple and multivariable regression models were used to examine associations between NR Total and subscale scores with dietary diversity scores and fruit and vegetable intake with NR Total scores and subscale scores. The multivariable models were adjusted for age, race, gender, and income. Results: People with higher NR Total ( P < .001), NR Self (P < .001), NR Perspective (P = .002), and NR Experience (P = .002) were more likely to report greater dietary diversity. Those with higher NR Total (P < .001), NR Self (P < .001), and NR Experience (P < .001) reported greater fruit and vegetable intake. Associations remained significant after adjusting for covariates. Conclusion: NR was associated with better dietary intake after accounting for socio-demographic indicators. These findings highlight the need for health promotion interventions that enhance NR, such as nature prescription initiatives, urban gardening and greening, and immersion in urban green spaces.